Combinatorial design of a sialic acid imprinted binding site exploring a dual ion receptor approach. Issue 54 (22nd October 2021) - Mavliutova, Liliia; Verduci, Elena; Sellergren, Börje
Abstract : Dual-ion imprinting of sialic acid via cooperatively acting ureido- and crown ether functionalities leads to charge neutral sialic acid receptors with strong sialoglycopeptide affinity. Abstract : Aberrant sialic acid expression is one of the key indicators of pathological processes. This acidic saccharide is overexpressed in tumor cells and is a potent biomarker. Development of specific capture tools for various sialylated targets is an important step for early cancer diagnosis. However, sialic acid recognition by synthetic hosts is often complicated due to the competition for the anion binding by their counterions, such as Na + and K + . Here we report on the design of a sialic acid receptor via simultaneous recognition of both the anion and cation of the target analyte. The polymeric receptor was produced using neutral (thio)urea and crown ether based monomers for simultaneous complexation of sialic acid's carboxylate group and its countercation. Thiourea and urea based functional monomers were tested both in solution by 1 H NMR titration and in a polymer matrix system for their ability to complex the sodium salt of sialic acid alone and in the presence of crown ether. Combination of both orthogonally acting monomers resulted in higher affinities for the template in organic solvent media. The imprinted polymers displayed enhanced sialic acid recognition driven to a significant extent by the addition of the macrocyclic cation host. The effect of various counterions and solvent systems on the binding affinities is reported. Binding of K +, Na + and NH4 + salts of sialic acid exceeded the uptake of bulky lipophilic salts. Polymers imprinted with sialic or glucuronic acids displayed a preference for their corresponding templates and showed a promising enrichment of sialylated peptides from the tryptic digest of glycoprotein bovine fetuin.